Frailty and health service use in rural South Australia. (January 2016) - Dent, Elsa; Hoon, Elizabeth; Karnon, Jonathan; Newbury, Jonathan; Kitson, Alison; Beilby, Justin
Highlights: This study investigated frailty in a rural South Australian community ( n  = 1501). Frailty was operationalized using the Frailty Index. Frail adults were more likely to visit specific health service providers. They were also more likely to report severe difficulties accessing health care. Abstract: Background: Frailty is a common geriatric condition, well known to contribute to morbidity and mortality. What is not yet well articulated in the literature is the health service use of frail older people in rural areas. This study investigated the impact of frailty on health service use in rural South Australia. Methods: This secondary cross-sectional analysis included people aged ≥65 years from the LINKIN health census in Port Lincoln. Frailty was classified using a Frailty Index (FI) score ≥0.25. Health service use was determined by patient questionnaire. All regression analyses controlled for age, gender and education level. Results: 1501 people [mean (SD) age = 75.9 (7.9)] years were included. Frailty prevalence was 25%, with this prevalence higher in females (29%) than in males (21%). Compared with their non-frail peers, frail adults were more likely to have consulted health providers, including: general practitioners (GPs) (odds ratio (OR), 95% confidence interval (CI = 2.09, 1.24–3.53); physiotherapists (OR, CI = 2.42, 1.80–3.25); mental health providers (OR, CI = 2.88, 1.42–5.85); community nurses (OR, CI = 2.57, 1.73–3.82); and dieticians (OR, CI = 2.77, 1.77–4.48). They were also more likely to have visited a health professional prior to a problem occurring (OR, CI = 1.51, 1.08–2.11), travelled to the city for a specialist appointment (OR, CI = 1.53, 1.11–2.11), and to have been hospitalised in the previous 12 months (OR, CI = 2.39, 1.74–3.29). Conclusion: Frail older adults were more likely to use several health services, yet often had unmet needs in their health care.